Indução de edema de boca em ratos como modelo de detecção de drogas anti-inflamatórias de ação local - Paula Ladeira Ortolani (2011)
The present study aimed to develop an experimental model of acute inflammation in oral cavity of rats, it has been considered as a standard of comparison the hind paw edema of the rats. The edema rating was performed in parallel to the extravasation of Evans blue, another indicator of inflammatory activity in tissues with the same conditions. The inflammation was induced in rats, Holtzman male, in the upper lip into the middle portion of the masseter muscle (cheek) on the right by a subcutaneous injection of 500 mg of -carrageenan (CG) and the hand side saline solution 0.9% was injected in the same volume. Measurements of the volume of edema was rated before edematogenic agent (0 hour) administration and after in ½, 1, 2, 3, 4 and 6 hours. While vascular permeability was estimated by extravasation of Evans blue onto the interstitial space, occurred on two occasions, with a previously to the maximum effect of carrageenan (15 min), and another occurred at the time of peak edema (1 hour). For the evaluation of anti-inflammatory action, conventional drugs of different types were administered: indomethacin (2 mg / kg), ibuprofen (20 mg / kg), celecoxib (12 and 30 mg / kg) and dexamethasone (1 mg / kg) 30 minutes before stimulation with the CG. All theses drugs showed a significant reduction of edema if it was compared with the control group. The rating of possible inflammatory mediators was also achieved through the administration of maleate pyrilamine (10 mg / kg, the antagonist of histamine H1 receptor) and maleate pizotifen acid (2 mg / kg, mixed antagonist of histamine and serotonin) whose had a significant inhibition of the inflammation in the first hour, confirming the action of the major mediators involved in the inflammatory edema in the hind paw. At the end of the study, it was possible to conclude that the oral edema responds with the same sensitivity of the hind paw edema to inflammatory drugs, non-steroidal and steroidal, and can detect drugs with potential anti-inflammatory activity even in the first hour, so thus a faster model.